2007
DOI: 10.1002/9780471729259.mc01e01s4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacteria in Mixed Biofilm Communities Using Denaturing Gradient Gel Electrophoresis (DGGE)

Abstract: Most microorganisms in nature, including those within biofilms, live in mixed populations. PCR‐based molecular genetic techniques are very useful in studying microbial diversity since unculturable as well as culturable organisms can be investigated. One such technique is denaturing gradient gel electrophoresis (DGGE), which separates PCR‐amplified community 16S rRNA (and other gene) sequences on the basis of G+C content. Unlike other community fingerprinting techniques, bands from DGGE gels can be excised, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, Noguchi et al have identified 113 biofilmforming bacterial species on root surfaces outside the apical foramen and associated with refractory periapical periodontitis [12]. More often, the denaturing gradient gel electrophoresis (DGGE) method is employed to separate PCR-amplified community 16S rRNA on the basis of G+C content [13]. This method is widely used by different research groups to describe the microbial diversity and phylogenetic affiliation, and to identify individual species in multi-species biofilms [14][15][16][17].…”
Section: Methods For Study Of Multiple-species Biofilmsmentioning
confidence: 99%
“…For example, Noguchi et al have identified 113 biofilmforming bacterial species on root surfaces outside the apical foramen and associated with refractory periapical periodontitis [12]. More often, the denaturing gradient gel electrophoresis (DGGE) method is employed to separate PCR-amplified community 16S rRNA on the basis of G+C content [13]. This method is widely used by different research groups to describe the microbial diversity and phylogenetic affiliation, and to identify individual species in multi-species biofilms [14][15][16][17].…”
Section: Methods For Study Of Multiple-species Biofilmsmentioning
confidence: 99%
“…Finally, the results from PCR identification of the microorganisms can increase patient's motivation to maintain good oral hygiene. Unlike the bacterial cultivation method, PCR technique is carried out at the nucleic acid level and it doesn't depend on living bacteria presence [19,24]. This means simple collection and transport of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular biology techniques have been developed and used for identification of the microbial organisms [14][15][16]. Polymerase chain reaction (PCR) is a simple technique which performs replication of a fragment from DNA and/or RNA and it has found its use in the detection of periodontopathic bacteria [17][18][19]. PCR doesn´t require living cells for identification of the microorganisms and offers significantly higher sensitivity than bacterial culture [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass accrual is used as an indicator for overall biofilm growth. Structural changes are currently measured either by using traditional species identification with light microscopy or with nucleotide-based techniques (e.g., denaturing gradient gel electrophoresis (DGGE), automated ribosomal intergenic spacer analysis (ARISA), metagenomics) 10,11,12 . These methods provide information but are timeconsuming to perform, or require specific knowledge, or are still under development.…”
Section: Introductionmentioning
confidence: 99%